Long COVID and lung thromboembolism in young adults - Araujo-Filho, Irami; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
Long-term COVID-19 (Long COVID) and pulmonary thromboembolism (PTE) significantly challenge healthcare, especially in young adults who are typically at lower risk for such severe outcomes. This review explores the complex relationship between long-term COVID and PTE, focusing on the pathophysiological mechanisms, diagnostic challenges, and therapeutic approaches. Persistent inflammation and immune dysregulation associated with long-term COVID-19 contribute to this demographic's increased thrombotic risk. The symptom overlaps between long-term COVID and PTE complicate the accuracy and timeliness of diagnoses, highlighting the necessity for improved diagnostic strategies. Findings emphasize the need for anticoagulation protocols tailored to the specific clinical presentations of Long COVID patients and suggest that extended treatment durations may be beneficial. The potential of genetic and biomarker research to identify individuals at heightened risk of thrombotic complications is discussed. The review calls for a multidisciplinary approach that integrates medical and psychosocial interventions to manage the long-term effects of COVID-19 effectively. As the pandemic evolves, advancing our understanding and adapting healthcare strategies to these insights are crucial for developing effective clinical practices. This is essential for addressing the immediate health impacts and reducing the broader socioeconomic burdens associated with long-term COVID and PTE in young adults.